Impact of a minimum tax rate under the Pillar Two solution on small island developing states - Kuldeep Sharma (South Centre, 2022)
The Research Paper commences with an overview of Pillar One and Pillar Two followed by detailed discussions on salient provisions of Pillar Two. Pillar Two is envisaged to have a widespread impact on Small Island Developing States (SIDS) which are a distinct group of 38 United Nations (UN) Member States and 20 Non-UN Members/Associate Members of UN regional commissions that are exposed to unique social, economic and environmental vulnerabilities. In all, 36 SIDS that are members of the Group of Seventy-Seven (G-77) have been analysed, namely, Antigua and Barbuda, Bahamas, Bahrain, Barbados, Belize, Cabo Verde, Comoros, Cuba, Dominica, Dominican Republic, Fiji, Grenada, Guinea-Bissau, Guyana, Haiti, Jamaica, Kiribati, Maldives, Marshall Islands, Mauritius, Federated States of Micronesia, Nauru, Papua New Guinea, Samoa, S\~ao Tomé and Príncipe, Seychelles, Singapore, Solomon Islands, St. Kitts and Nevis, St. Lucia, St. Vincent and the Grenadines, Suriname, Timor-Leste, Tonga, Trinidad and Tobago, and Vanuatu.
Keywords: 300; Automatic Exchange of Information (AEOI); Bahamas; Bahrain; Barbados; Base Erosion and Profit Shifting Project (BEPS); Belize; Common Reporting Standard (CRS); Corporate Income Tax (CIT); De Minimis Exclusion; Digital Economy; Digital Tax; Digital Taxation; Digitalisation of the Economy; Foreign Direct Investment (FDI); Global Anti-Base Erosion (GloBE) Rules; Global Minimum Tax Rate; Global Tax; Global Taxation; Group of 77 and China (G-77 and China); Inclusive Framework; International Shipping Income; International Tax; International Tax Cooperation; International Taxation; Maldives; Multilateral Competent Authority Agreement (MCAA); Offshore Financial Centres (OFCs); Organisation for Economic Co-operation and Development (OECD); Pillar One; Pillar Two; Qualified Domestic Minimum Top-up Tax (QDMTT); Small Island Developing States (SIDS); Subject to Tax Rule (STTR); Tax; Tax Competition; Tax Cooperation; Tax Havens; Tax Incentive; Tax Law; Tax Policy; Tax Reform; Taxation; Transfer Pricing; Two Pillar Solution; United Arab Emirates (UAE); United Nations (UN)